Defying the odds: A self-reflection of an Indigenous woman lawyer with a disability in Ghana - Esther Akua Gyamfi (Disability Studies Quarterly, 2022)
No abstract available.
Keywords: care; discrimination; education; Ghana; identity; Indigenous; kinship; law